El conejo y el coyote - Kohen, Clarita, 1943-; Menicucci, Gina (Boston, MA : Houghton Mifflin, 1997)
In this rhyming adaptation of the traditional Mexican tale, the coyote tries to trick the rabbit with humorous results.
Keywords: Folklore -- Mexico; Stories in rhyme; Spanish language materials; Juvenile literature